2021
DOI: 10.1080/17441692.2021.1964559
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising men’s role and participation in PMTCT programmes in Malawi and Zambia: A hegemonic masculinity perspective

Abstract: This study sought to explore and contextualise the man's role in antenatal services, and the barriers and strategies for engaging men in prevention of mother-to-child HIV transmission (PMTCT). We conducted 143 interviews with pregnant and breastfeeding women, male partners, health workers and policy makers in Malawi and Zambia. We employed thematic and critical discourse analysis using the hegemonic masculinity perspective. We found that men's roles in PMTCT reflected hegemonic masculinities. As breadwinners, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…As such, participants in our study proposed that the health system needs to go beyond the traditional ‘go and bring your husband’ agenda by extending a direct appeal to men through health and gender sensitive messaging. While this recommendation is consistent with recent study implications in Malawi and Zambia(53), it is in stark contrast to a study in Tanzania in where participants proposed that women should bear the emotional and intellectual burden of involving their partners in maternal and child health(54).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As such, participants in our study proposed that the health system needs to go beyond the traditional ‘go and bring your husband’ agenda by extending a direct appeal to men through health and gender sensitive messaging. While this recommendation is consistent with recent study implications in Malawi and Zambia(53), it is in stark contrast to a study in Tanzania in where participants proposed that women should bear the emotional and intellectual burden of involving their partners in maternal and child health(54).…”
Section: Discussionsupporting
confidence: 80%
“…The corresponding author (LHF)— conducted the majority of SSIs (53) and co-facilitated all FGDs. LHF was assisted by a female Bachelor’s degree nurse midwife and a female master’s level sociologist who served as co-interviewers, observers and note-takers during group discussions.…”
Section: Methodsmentioning
confidence: 99%
“…The level of male partner support may influence women's decision to take PrEP during pregnancy and breastfeeding. Evidence suggests that men are generally viewed as head of house and ultimate decision makers who are actively involved in health-related decision-making during pregnancy and breastfeeding ( 47 , 48 ). Our study found that women had divergent views about who would approve of their decision to take PrEP during pregnancy and breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in similar settings. In a study that contextualized male roles and participation in PMTCT programs in Malawi and Zambia, for instance, both men and women reported that they had to consult and seek approval from their partners on decisions that related to their health ( 47 ). Other studies also reported that men were the primary advisors and key decision-makers on health-related decisions during pregnancy and breastfeeding ( 41 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to focus on Malawi and Zambia due to their high HIV burdens and our ongoing HIV prevention work http://onlinelibrary.wiley.com/doi/10.1002/jia2.26128/full | https://doi.org/10.1002/jia2.26128 among ANC patients and their partners in these countries [10][11][12][13][14]. While specific quantitative results are most applicable to the populations of these countries, we expect that our findings are broadly generalizable to other eastern and southern African settings with similar patterns of sexual behaviour, HIV status awareness, viral suppression and ANC utilization.…”
Section: Discussionmentioning
confidence: 99%